LOOKED AFTER CHILDREN’S PERSPECTIVES ON BOOKS BEING DELIVERED TO THE HOME DURING THE LETTERBOX CLUB SCOTLAND PROJECT - Andy Hancock; Juliet Hancock (International Journal of Child, Youth & Family Studies, 2017)
The low educational achievement of looked after children — children in the care of a local authority — is well documented in the United Kingdom and internationally. However, official statistics do not reveal the nuances of individual children’s lived experiences nor children’s agency. This article gives weight to children’s perspectives, and reports on the views of looked after children aged 7 to 10 in Scotland during the Letterbox Club project. It specifically investigates children’s perspectives of reading practices in the home and their responses to books delivered to them over a 6-month period. Data were gathered from 3 distinct but interrelated phases of the research: (a) literacy profiles completed by the children in collaboration with their carer(s), (b) children’s comments on evaluation sheets contained in each of the six parcels, and (c) individual conversations with children at the end of the project. The findings reveal the heterogeneous nature of looked after children with multifarious reading proficiencies and reading habits and routines. The children made choices about where and when they read and with whom, expressing opinions about books and authors and using the contents of the parcels to take action and gain greater ownership of their own learning. Finally, the contested nature of children’s agency is discussed, as well as the implications for future research involving looked after children.